2019
DOI: 10.1002/jcp.29246
|View full text |Cite
|
Sign up to set email alerts
|

HOXC10 promotes cell migration, invasion, and tumor growth in gastric carcinoma cells through upregulating proinflammatory cytokines

Abstract: HOXC10 plays a critical role in many cellular processes, such as proliferation, migration, and invasion, but the function of HOXC10 in gastric carcinoma is not clear.In this study, we aimed to investigate the expression profile of HOXC10 and its role in gastric carcinoma cells and in vivo experiments. HOXC10 expression patterns were detected in clinical samples and gastric cancer cells lines by reverse transcriptase polymerase chain reaction assays, and then, we focused on its role in regulating cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…( 51 ) found that high levels of HOXC10 in gastric cancer tissues were significantly associated with worse prognosis, as well as hepatic and peritoneal recurrence. And the studies confirmed that HOXC10 can cooperate with inflammatory cytokines ( 58 ), ATM/NF-κB axis ( 57 ), and EMT ( 60 , 64 , 65 ) to promote tumor migration and invasion. High HOXC10 expression can also induce tumor drug resistance by increasing DNA repair activity ( 52 , 53 ).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 73%
See 3 more Smart Citations
“…( 51 ) found that high levels of HOXC10 in gastric cancer tissues were significantly associated with worse prognosis, as well as hepatic and peritoneal recurrence. And the studies confirmed that HOXC10 can cooperate with inflammatory cytokines ( 58 ), ATM/NF-κB axis ( 57 ), and EMT ( 60 , 64 , 65 ) to promote tumor migration and invasion. High HOXC10 expression can also induce tumor drug resistance by increasing DNA repair activity ( 52 , 53 ).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 73%
“…Li et al. confirmed that HOXC10 silencing suppressed metastasis and invasion, whereas HOXC10 overexpression significantly enhanced metastasis in gastric cancer cell lines ( 58 ). These studies suggested that HOXC10 may be a novel biomarker of metastasis, invasion, and recurrence after radical resection of gastric cancer.…”
Section: Tumor Metastasis and Invasionmentioning
confidence: 97%
See 2 more Smart Citations
“…HOXC10 is a target of miR-129-5p, and miR-129-5p inhibits gastric cancer development by regulating HOXC10/Cyclin D1 axis [22]. HOXC10 is highly expressed in the poorly differentiated gastric carcinoma cells, and it accelerates proin ammatory cytokines through NF-κB signaling pathway to promote the progression of gastric carcinoma [23]. In liver cancer, HOXC10 expression is markedly decreased.…”
Section: Discussionmentioning
confidence: 99%